2003
DOI: 10.1096/fj.02-0518com
|View full text |Cite
|
Sign up to set email alerts
|

Direct gene transfer into rat articular cartilage by in vivo electroporation

Abstract: To establish a system for efficient direct in vivo gene targeting into rat joint, we have evaluated a strategy of gene transfer by means of the delivery of external electric pulses (EP) to the knee after intra-articular injection of a reporter gene (GFP). Rats were killed at various times after the electro gene-therapy to analyze GFP gene expression by immunohistochemistry. GFP staining was detected in the superficial, middle, and deep zones of the patellar cartilage at days 2 and 9, and thereafter only in the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
36
0

Year Published

2004
2004
2016
2016

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 43 publications
(39 citation statements)
references
References 28 publications
3
36
0
Order By: Relevance
“…Thus, one can imagine a biological targeting of inflammation sites via the homing at inflammatory sites of lymphocytes pre-transfected in the spleen. In order to reach local production of cytokines too, a study with the GFP reporter gene demonstrated the feasibility of electroporation to the knee after intraarticular injection [90]. Until now, most of the studies realized on other organs, such as cornea [14], tendon [12], liver [11], bladder [13], brain [17], etc., have focused on vector development and establishment of transfer techniques.…”
Section: Electrotransfer In Other Tissuesmentioning
confidence: 99%
“…Thus, one can imagine a biological targeting of inflammation sites via the homing at inflammatory sites of lymphocytes pre-transfected in the spleen. In order to reach local production of cytokines too, a study with the GFP reporter gene demonstrated the feasibility of electroporation to the knee after intraarticular injection [90]. Until now, most of the studies realized on other organs, such as cornea [14], tendon [12], liver [11], bladder [13], brain [17], etc., have focused on vector development and establishment of transfer techniques.…”
Section: Electrotransfer In Other Tissuesmentioning
confidence: 99%
“…Gene therapeutics lead to an inherent sustained release of expressed therapeutic genes by host cells in situ, which is more effective due to higher bioactivity of the hostproduced growth factor (Bonadio et al, 1999;Bleiziffer et al, 2007). Plasmid DNA has been successfully applied in direct in vivo gene transfer for wound healing and angiogenesis (Michlits et al, 2007;Mittermayr et al, 2008), cardiac regeneration (Sundararaman et al, 2011) and musculoskeletal regeneration (Grossin et al, 2003;Kawai et al, 2006;Osawa et al, 2009;Osawa et al, 2010). Taking these advantages into account, non-viral vectors, such as plasmid DNA, are considered the most likely candidates for clinical translation of tissue regenerative gene therapies.…”
Section: Introductionmentioning
confidence: 99%
“…The majority of these studies were gene therapy studies, such as siRNA or protein delivery into chondrogenic cell lines, or, animal models of arthritis [11][12][13] . In other systems, such as chicken or mouse, electroporation of facial mesenchyme has been challenging (personal communications, Dept of Craniofacial Development, KCL).…”
Section: Introductionmentioning
confidence: 99%